The impact of COVID-19 response measures on the quality of life for children in the Eastern Mediterranean region using an exposome approach: A narrative review - Haddad, Nadine; Abou Naja, Hala; Makris, Konstantinos C. (My University, 2021)
Background There is a consensus that children’s needs have not been sufficiently prioritized during the COVID-19 pandemic, and their right to a safe and healthy childhood has been compromised to an extent, worldwide. A comprehensive assessment of population- and individual-level changes associated with COVID-19 and its pandemic response measures could be undertaken using the human exposome concept. The exposome is defined as the totality of environmental exposures from conception onwards, including the endogenous response. The objective of this study was to conduct a narrative review using an exposome approach exploring short-term changes in the children’s exposome profile (<18 years old) associated with the COVID-19 measures implemented in the Eastern Mediterranean region (EMR). Methods Google Scholar, PubMed and Reliefweb databases were searched for original studies and situation reports published in English between January 1, 2020 and January 31, 2021, pertinent to the EMR countries. Publications describing a quantitative or qualitative impact of the COVID-19 pandemic measures on children were summarized using the three exposome domains: General external (policies and programs), specific external (lifestyle and environmental contaminants) and internal (intrinsic properties, metabolism, etc.). Results Out of 405 results generated from PubMed and Google Scholar and 687 reports identified from Reliefweb, a total of 16 original research articles and 36 situation reports were retained, involving 14 out of 22 EMR countries. Most publications documented the impact of COVID-19 pandemic measures on children’s general and specific external exposome domains, while few studies dealt with the internal domain (risk of stunting, malnutrition). In effect, chronic efforts by national and international programs to tackle historical EMR challenges of child protection from labor, displacement, trauma and violence, promotion of education, and eradication of pediatric malnutrition and infectious diseases seem to be at risk during the COVID-19 crisis, either due to inaction or suspension of children’s services and programs. Conclusions Regional authorities and governmental bodies are pledged to assess the impact of the wider array of COVID-19 response measures on children’s exposome profile. A prompt deployment of multi-sectoral COVID-19 recovery plans is warranted for the benefit of the children in the EMR region.
Keywords: Lockdown; Children; Non-pharmacological interventions; Exposome; Covid-19